2011
DOI: 10.1007/s12265-011-9325-8
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Omega-3 Polyunsaturated Fatty Acids and Survival in Patients with Chronic Heart Failure and Major Depressive Disorder

Abstract: The omega-3 fatty acid (FA) concentration is low in patients with coronary heart disease (CHD). Supplement of omega-3 FA improves cardiovascular outcomes in patients with CHD and heart failure (HF). However, plasma omega-3 FA and its role for prognosis in HF patients have not been examined previously. In this study, we explore the prognostic value of omega-3 polyunsaturated FA in HF patients with major depressive disorder (MDD). Plasma was obtained from HF patients with MDD who participated in the Sertraline A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 56 publications
0
11
0
3
Order By: Relevance
“…Briefly, a total of 493 independent citations were identified after duplicate exclusion, of which 32 were retrieved for full-text review. Ten publications were excluded because the exposure or outcome was not relevant to the topic we studied; 11 reports were excluded because they investigated dietary/circulating n-3 LCPUFA among patients with certain diseases, such as type 2 diabetes2324, CHD25262728, heart failure2930, and kidney disease313233; further excluded was one publication34 which was an overlapping report of another35 with larger events. Finally, 10 publications13141516171819202122 including 11 independent prospective studies (2 cohorts were combined in one publication17) were included in this meta-analysis, involving 7 studies131415161718 on dietary n-3 LCPUFA and 4 studies19202122 on circulating EPA/DHA in relation to all-cause mortality risk.…”
Section: Resultsmentioning
confidence: 99%
“…Briefly, a total of 493 independent citations were identified after duplicate exclusion, of which 32 were retrieved for full-text review. Ten publications were excluded because the exposure or outcome was not relevant to the topic we studied; 11 reports were excluded because they investigated dietary/circulating n-3 LCPUFA among patients with certain diseases, such as type 2 diabetes2324, CHD25262728, heart failure2930, and kidney disease313233; further excluded was one publication34 which was an overlapping report of another35 with larger events. Finally, 10 publications13141516171819202122 including 11 independent prospective studies (2 cohorts were combined in one publication17) were included in this meta-analysis, involving 7 studies131415161718 on dietary n-3 LCPUFA and 4 studies19202122 on circulating EPA/DHA in relation to all-cause mortality risk.…”
Section: Resultsmentioning
confidence: 99%
“…Due to limited blood volume following the metabolomics and the lipidomics studies 33,34 , adequate blood sample volume suitable for this inflammatory biomarker study was only available for 157 of the 175 subjects. Two subjects were missing data for important covariates resulting in a final sample size of 155: 130 from the MDD groups (Mild: n = 48; Moderate: n =49; and Severe: n = 33) and 25 from the none-depressed group.…”
Section: Resultsmentioning
confidence: 99%
“…Depression remains poorly detected despite its prevalence and its association with increased mortality [173], as symptoms of depression can overlap with those of heart failure. Interestingly, some authors have suggested that low plasma omega-3 fatty acid is a factor for reduced survival in CHF patients with depression [174]. Vigilant survey with screening tools such as patient health questionnaire can aid detection of depression in CHF patients [175].…”
Section: Depressionmentioning
confidence: 99%